Ultra-peripheral collisions of charged hadrons in extensive air showers - Masip, Manuel (2023)
We discuss the electromagnetic collisions of high energy protons, pions and kaons with atmospheric nuclei. In particular, we use the equivalent photon approximation to estimate (i) the diffractive collisions where the projectile scatters inelastically off a nucleus, and (ii) the usual radiative processes (bremsstrahlung, pair production and photonuclear interactions) of these charged hadrons in the air. We then include the processes in the simulator AIRES and study how they affect the longitudinal development of extensive air showers. For 109-11 GeV proton primaries we find that they introduce a very small reduction (below 1%) in the average value of both X max and ΔX max. At a given shower age (relative slant depth from X max), these electromagnetic processes slightly increase the number of charged particles at the shower maximum and reduce the number of muons when it is old, decreasing by 1% the muon-to-(γ + e) near the ground level.